2021
DOI: 10.1177/21650799211003562
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Evaluation of Scapular Dyskinesis Among Professional Bus Drivers With Unilateral Upper Quadrant Musculoskeletal Pain

Abstract: Background: Professional bus drivers report a high prevalence of upper quadrant musculoskeletal pain which could be associated with scapular dyskinesis (SD). However, the evidence for valid and reliable screening methods for this condition is limited as SD among bus drivers is an emerging area of research. Therefore, the main aim of the study was to investigate the reliability of dynamic scapular motion test (DSMT) using video analysis as an accurate method to evaluate SD and to identify patterns of SD among b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The different methods and levels of SE in WRMSD identified in this review might provide information to policy makers, researchers, and organisations in establishing guidelines for engaging stakeholders in WRMSDs care and research agenda. As the SMART Drive network group is currently engaging with various stakeholders as part of developing a comprehensive care and related policies to manage WRMSD in a group of professional drivers (Kasemsan, 2021, Sattasuk, 2021, the findings of the study have direct implications in terms of implementing the methods and levels of SE identified in the current review.…”
Section: Discussionmentioning
confidence: 98%
“…The different methods and levels of SE in WRMSD identified in this review might provide information to policy makers, researchers, and organisations in establishing guidelines for engaging stakeholders in WRMSDs care and research agenda. As the SMART Drive network group is currently engaging with various stakeholders as part of developing a comprehensive care and related policies to manage WRMSD in a group of professional drivers (Kasemsan, 2021, Sattasuk, 2021, the findings of the study have direct implications in terms of implementing the methods and levels of SE identified in the current review.…”
Section: Discussionmentioning
confidence: 98%
“…Studies about upper quadrant musculoskeletal disorders in various occupations with ergonomic risk factors, such as prolonged static position and repeated upper limb-based activities for long hours as bus drivers, workers on sewing machines, and mechanics, described the prevalence of upper body pain as being associated with age under 30, female gender, having a diagnosis of an MSD or a systemic illness, working for more than 10 years, higher work-rest ratios, and high physical exertion (54). Additionally, 53% of bus drivers have dyskinesia, which has been linked to unilateral upper quadrant musculoskeletal pain that has been explained by repetitive neck and shoulder motions over an extended period of time and overuse (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…The ethical approval for the study was obtained from a university institutional ethics committee, according to the Declaration of Helsinki (Ethical approval number AMSE-64EX-112). This study was a continuation of the initiatives from the Sustainable Measures for Assessment and Rehabilitation Drive (SMART Drive) research networking group which had been working on a series of projects to enhance and improve musculoskeletal health and wellbeing for people at the work place (Joseph L et al 2020;Joseph L et al 2021;Kasemsan et al 2021;Sattasuk et al 2021).…”
Section: Study Design and Settingmentioning
confidence: 99%